A CASE OF INCARCERATION OF A HUGE INGUINAL HERNIA - ASAKAGE, Naoki; SASAKI, Morio; TSUKADA, Kenji; SUZUKI, Takahisa; GOTO, Tatsuya; KOBAYASHI, Shigeru (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2005)
We report a case of incarceration of a huge inguinal hernia which was difficult to treat. A 63-year-old man who had noticed swelling on the right side of the scrotum since 10 years previously but left it alone despite its tendency to increase. He had a 2-year history of medical treatment for bronchial asthma. He presented in the evening because stools with mucus and blood and lower abdominal pain which had occurred in the early morning became aggravated. When he was seen, prominent bulging from the right inguinal region to the scrotum was noted and the fundus of the scrotum reached an area just above the right knee joint when in a recumbent position. There was severe tenderness, mainly in the right lower abdomen. Abdominal plain x-ray and abdominal CT scan showed ileus findings as well as intestinal gas extending from the right inguinal region to inside the scrotum. Accordingly incarceration of a huge right inguinal hernia was diagnosed and an emergency operation was performed. When the inguinal region was incised and the inguinal duct was released, prolapse of about 300cm of intestine from the jejunum to the ascending colon was recognized and a part of the jejunum had become necrotic. Since hernia reduction was impossible by means of the inguinal method, a median incision on the upper abdomen was added and the prolapsed intestine was reduced into the abdominal cavity. The hernia hilum was fist-sized or larger and was repaired using a PROLINE® hernia system (size L). After the operation his respiratory condition became worse due to attacks of bronchial asthma which might have resulted from a postoperative increase in intraabdominal pressure. The patient had to stay in bed and required careful perioperative management, including prevention of deep venous thrombosis.